Cloud Computing and Big Data: Technologies, Applications and Security - Zbakh, Mostapha; Essaaidi, Mohammed; Manneback, Pierre; Rong, Chunming; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This book addresses topics related to cloud and Big Data technologies, architecture and applications including distributed computing and data centers, cloud infrastructure and security, and end-user services. The majority of the book is devoted to the security aspects of cloud computing and Big Data. Cloud computing, which can be seen as any subscription-based or pay-per-use service that extends the Internet's existing capabilities, has gained considerable attention from both academia and the IT industry as a new infrastructure requiring smaller investments in hardware platforms, staff training, or licensing software tools. It is a new paradigm that has ushered in a revolution in both data storage and computation. In parallel to this progress, Big Data technologies, which rely heavily on cloud computing platforms for both data storage and processing, have been developed and deployed at breathtaking speed. They are among the most frequently used technologies for developing applications and services in many fields, such as the web, health, and energy. Accordingly, cloud computing and Big Data technologies are two of the most central current and future research mainstreams. They involve and impact a host of fields, including business, scientific research, and public and private administration. Gathering extended versions of the best papers presented at the Third International Conference on Cloud Computing Technologies and Applications (CloudTech'17), this book offers a valuable resource for all Information System managers, researchers, students, developers, and policymakers involved in the technological and application aspects of cloud computing and Big Data. .
Elliptic Curve Qu-Vanstone based signcryption schemes with proxy re-encryption for secure cloud data storage -- Cloud Computing: Overview and Risk Identification Based on Classification by Type -- Authentication Model for Mobile Cloud Computing Database Service -- FADETPM: Novel Approach of File Assured Deletion Based on Trusted Platform Module -- Issues and Threats of Cloud Data Storage -- Challenges of Crowd Sensing for Cost-effective Data Management in the Cloud -- On the Security of Medical Image Processing in Cloud Environment -- Implementations of Intrusion Detection Architectures in Cloud Computing -- Privacy in Big Data Through Variable t-Closeness for MSN Attributes -- The Big Data-RTAP: Toward a Secured Video Surveillance System in Smart Environment -- Optimizations in Fully Homomorphic Encryption -- Support Cloud SLA establishment using MDE -- A New Parallel and Distributed Approach for Large Scale ImagesRetrieval -- Classification of Social Network Data Using a Dictionary-Based Approach -- Parallel and Distributed Map-Reduce Models for External Clustering Validation Indexes -- Workflow Scheduling Issues and Techniques in Cloud Computing: A Systematic Literature Review -- A Review of Green Cloud Computing Techniques -- Towards a smart exploitation of GPUs for low energy motion estimation using Full HD and 4K Videos -- Machine Learning applications in supply chains: Long Short-Term Memory for demand forecasting -- Performance Analysis of Preconditioned Conjugate Gradient Solver on Heterogeneous (Multi-CPUs/Multi-GPUs) Architecture -- Runtime prediction of optimizers using improved support vector machine -- AND/OR directed graph for dynamic web service composition -- An NLP based text-to-speech synthesizer for Moroccan Arabic -- Context-Aware Routing Protocol for Mobile WSN : Fire Forest Detection. .
Keywords: Mechatronics; Computational intelligence; Mechatronics; Computational Intelligence